ANALISA KOMPARASI PRODUKTIVITAS KERJA ANTARA PEMBATIK HARIAN DAN PEMBATIK LEPAS ( STUDI KASUS DI KAMPOENG BATIK LAWEYAN SURAKARTA) - Rahma Khairun Nisa; Siti Maryam; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2020)
The objective to be achieved through this research is to find out the differences in productivity of daily batik workers and loose batik workers. In addition, it is also to find out whether there are differences in work motivation, work experience between daily batik and loose batik in Kampoeng Batik Laweyan Surakarta. The method used is a comparative descriptive method. The population in this study amounted to 665 batik and the sample used amounted to 100 people, where the sampling technique uses purposive sampling and convenience sampling techniques. The data used are secondary data and primary data with data collection techniques of observation, questionnaires, interviews. documentation and study of literature. Data analysis techniques in this study used the Independent T-test. Based on the results of research and discussion shows there are significant differences in work productivity between daily batik and loose batik, there are differences in work motivation and work experience of daily batik and loose batik. Keywords: Work Productivity, Work Motivation and Work Experience